Incremental Introduction of Organocatalytic Activity into Conformationally Engineered Porphyrins - Senge, Mathias; Kielmann, Marc; Grover, Nitika; Kalisch, Werner W. (My University, 2019)
To study the correlation of macrocycle nonplanarity and catalytic activity of free base porphyrins in detail, a series of six tetraphenylporphyrins with graded degree of β‐ethyl substitution (“H2EtxTPPs” 1–6; x = 0, 2, 4, 6, 8) was applied in organocatalyzed reactions. The macrocycles display incrementally increasing nonplanarity due to repulsive peri‐interactions. This creates an out‐of‐plane vector and better accessibility of the core amine and imine groups as the number of alkyl substituents increases. Following such a molecular engineering approach, the inner core system could be used to activate small molecules as a result of significant saddle distortion. The potential organocatalyst “H2EtxTPPs” were used in benchmark sulfa‐Michael reactions and we found a distinct relationship between nonplanarity and conversion. These observations were attributed to the combined effect of enhanced basicity and increased H‐bonding potential that could facilitate bifunctional organocatalysis. Ultimately, density functional theory (DFT) calculations were performed on 1–6 to monitor some electronic properties of the title compounds.
Keywords: Hydrogen bonds; Macrocycles; Molecular engineering; Organocatalysis; Porphyrins